Advances in Computer Science for Engineering and Education - Hu, Zhengbing; Petoukhov, Sergey; Dychka, Ivan.; He, Matthew; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book features high-quality, peer-reviewed research papers presented at the First International Conference on Computer Science, Engineering and Education Applications (ICCSEEA2018), held in Kiev, Ukraine on 18-20 January 2018, and organized jointly by the National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute" and the International Research Association of Modern Education and Computer Science. The state-of-the-art papers discuss topics in computer science, such as neural networks, pattern recognition, engineering techniques, genetic coding systems, deep learning with its medical applications, as well as knowledge representation and its applications in education. It is an excellent reference resource for researchers, graduate students, engineers, management practitioners, and undergraduate students interested in computer science and their applications in engineering and education.
Chapter 1. Physical and Mathematical Modeling of Permeable Breakwaters (Lidiia Tereshchenko, Vitalii Khomicky, Ludmyla Abramova, Ihor Kudybyn, Ivan Nikitin, Igor Tereshchenko) -- Chapter 2. Risk Modeling of Accidents in the Power System of Ukraine with Using Bayesian Network (Viktor Putrenko, Nataliia Pashynska) -- Chapter 3. Influence of the Deep Spherical Dimple on the Pressure Field under the Turbulent Boundary Layer (V.A. Voskoboinick, V.N. Turick, O.A. Voskoboinyk, A.V. Voskoboinick, I.A. Tereshchenko) -- Chapter 4. Structural Model of Robot-manipulator for the Capture of Non-cooperative Client Spacecraft (D. Humennyi, I. Parkhomey, M. Tkach) -- Chapter 5. The Designing and Research of Generators of Poisson Pulse Sequences on Base of Fibonacci Modified Additive Generator (Volodymyr Maksymovych, Oleh Harasymchuk, Ivan Opirskyy) etc.
Keywords: Computational intelligence; Educational technology; Computational Intelligence; Digital Education and Educational Technology